Gerakan Sosial Pelestarian Lingkungan Hidup Perspektif Struktural Fungsional (Kontribusi Benua Lestari Indonesia di Kota Tanggerang) - Hayati Harahap, Rahma; Meysari BR Tarigan, Devika (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Basically, the relationship between nature and humans is an interdependent relationship with each other. A balanced relationship between nature and humans can form a good system. However, the fact is that environmental problems occur in various regions in Indonesia. People's habit of exploiting ingrained nature makes nature and the environment worse. The main idea in this study is the realization of the balance of the relationship between humans and nature through the formation of a social movement for environmental conservation. This study aims to review the existence of social movements and contributions in building environmental conservation and improving sustainable ecosystems. This research uses the knife analysis of sociological of human ecology, namely a functional structural perspective. This research uses a literature method that contains theories related to the problem under study and literature studies from various studies. The sources of data used in this study are scientific articles and previous research. The results showed that the social movement for environmental conservation carried out by the Sustainable Continent of Indonesia together with the people of Tanggerang City through concrete actions to care for the environment is a manifestation of the balance of the system between humans and nature as meant by a functional structural perspective. Ecosystem care actions are carried out in an effort to preserve the environment and pay attention to environmental sustainability for common life. The social movement of environmental conservation carried out in Tanggerang City can be an example of good implementation of nature for all Indonesian people.